Analysis of 11Be + p elastic scattering using a BHF approach. (19th September 2017) - Sharma, Manjari; Haider, W; Bhagwat, A
Abstract: The elastic scattering of the halo nucleus 11 Be on the proton at various incident energies has been analysed using the microscopic optical potential (OP) calculated within the first order non-relativistic Brueckner–Hartree–Fock (BHF) approach. Argonne v-18 inter-nucleon potential is employed to calculate the microscopic OP. The nuclear density distribution has been obtained using a semi-phenomenological model. The density used shows extended neutron distribution indicating a possible halo structure. We have also compared our results with an empirical analysis using CH89 global OP. The analysis reveals that the BHF approach provides good agreement with the experimental data for all incident energies considered in this paper.